THE EFFECT OF GROWTH AND PRODUCTION OF PAKCHONG GRASS (PENNISETUM PURPUREUM CV THAILAND) WITH THE APPLICATION OF LIQUID ORGANIC FERTILIZER (POC) FERMENTED WITH EM4 - Insyafillah, Mhd; Sembiring, Meriksa (Agropet, 2025)
This study aims to determine the effect of giving liquid organic fertilizer POC goat urine fermented with EM4 (Effective Microorganisms) with different concentrations on the productivity of Pakchong grass (Pennisetum purpureum cv. Thailand). The design of this study used a non-factorial Randomized Block Design consisting of 5 treatments and 5 replications. The treatments given consisted of five types, namely: P0 as a control using urine without fermentation, P1 using urine fermented with EM4 as much as 1%, P2 using urine fermented with EM4 as much as 2%, P3 using urine fermented with EM4 as much as 3%, and P4 using urine fermented with EM4 as much as 4%. Response to Pakchong grass by applying the fermentation results to each treatment with 50 ml/stem by sprinkling it around the stem for each treatment. The first fertilization of POC was done after 2 weeks after planting and was done 3 times with an interval of 1 week 1 week before harvest. The parameters observed were height increase, number of tillers, leaf length, leaf width, and fresh and dry forage production. Data from observations and measurements were analyzed statistically, if there was a significant difference then continued with testing using DMRT. The results of the analysis of the parameters observed from the effect of several uses of POC from goat urine showed a significant difference (p <0.05) on the parameters used, with the results that the higher the concentration of EM4 used, the better the parameters.